PERKEMBANGAN EKSPOR LAMPIT ROTAN DI PROPINSI KALIMANTAN SELATAN - Setiasih Irawanti (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
Floor mats iB the main export commodity from South Kalimantan Province. The decrease of floor mats export demand from thiB province since the end of 1988 indicates the beginning of busine• slow down period of (loo'lt.. mats.The study results using multiple regreBBion analysiB, showed that among four variablesi.e. yen exchange rute against the US dollar (X1), interest rate in apan (Xa), t. he Indonesian government po_l to su11_port e port of (iniBhed products nattan (Xa) ai1d change of season in Japan (X4), ,only two variablesgave a szgnlficant impact on the floor mats esport volume (denoted by Y). These two variablesare the yen exchange rate against US dollar (X 1) and the season (X4'. The relationship can be expreued by a multiple regresion equation as follows : In Y - 21.4608-3.0463 In x1-o.6206 In x2+0.2744 x3+0.7537 X4+E with the coefficient of determination (R2) of 0,6367.